Reducing Heart dose during Left Breast Cancer Radiotherapy: Comparison among 3 Radiation Techniques. Issue 2 (March 2016) - D'Agostino, Giuseppe R.; Diletto, Barbara; Mantini, Giovanna; Nardone, Luigia; Mattiucci, Gian Carlo; Catucci, Francesco; Canna, Roberta; Martino, Antonella; Azario, Luigi; Valentini, Vincenzo
Purpose: Breast cancer survivors have a high risk of cardiac death as a consequence of heart irradiation during left breast tangential radiotherapy (RT). This study compares the cardiac dose delivered by standard 3D conformal tangential RT (CRT) to that delivered by prospective-gating RT (PGRT) or 5-field intensity-modulated RT (IMRT). Methods: Patients with early left breast cancer, referred for adjuvant RT to our institution, were enrolled in this study. For each patient, 2 simulation computed tomography scans were acquired: the first during free breathing, and the second on prospective gating during deep inspiration breath-hold. The scans were monitored by the Varian RPM™ respiratory gating system. For each patient, 3 treatment plans were performed: a 3D-CRT and an IMRT plan, each based on the free-breathing scan, and a PGRT plan, based on the deep inspiration breath-hold scan. Dose-volume histograms were compared by means of the Friedman test. Results: The median mean heart dose was 3 Gy (range 0.9-7.3 Gy) in the CRT plans, 1.9 Gy (range 0.5-3.6 Gy) in the PGRT plans, and 4.5 Gy (range 1.1-10.5 Gy) in the IMRT plans (p = 0.001). The mean heart V25 was 1.2% (range 0%-9.7%), 0% (range 0%-2.0%), and 0.2% (range 0%-7.3%) for CRT, PGRT, and IMRT plans, respectively (p<0.001). Conclusions: Prospective-gating RT to the left breast offered the best protection of heart and lung, as well as a lower irradiation of the contralateral breast, compared to CRT or IMRT.